EDITORIAL PREFACE (Volume 6, Issue 1, November 2018) - Pangaribuan, Christian Haposan (Journal of Business And Entrepreneurship, 2018)
Journal of Business and Entrepreneurship, Volume 6, Issue 1, May 2018.